Characterization of thermal and material properties of solid-state composite eco-briket from domestic waste and coconut shells - Aisiyah, Muktamar Cholifah; Bait, Jennifer Farihatul (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2025)
Municipal solid waste continues to pose a significant environmental and logistical challenge in rural regions of Indonesia, particularly due to limited landfill capacity and insufficient public engagement in waste management. This research aims to evaluate the effectiveness of solid-state composite eco-briquette technology as an alternative solution for optimizing waste handling at TPS 3R Lestari Desaku, Lamongan Regency. The study involved systematic waste segregation, carbonization of organic residues and coconut shells via controlled pyrolysis, and briquette fabrication using a 1:1 biochar blend and a 10% starch binder. Thermal and material characterizations were conducted following ASTM standard methods and benchmarked against Indonesian National Standards (SNI 01-6235-2000). The results revealed that the produced briquettes had high fixed carbon content (84%), low ash (1.72%) and moisture (6.15%), and a calorific value of 7411.76 cal/g, well above the SNI minimum threshold. These findings indicate that the briquettes possess strong thermal performance and structural integrity. The project also highlighted the potential of integrating physics-based waste valorization processes into community-level waste management systems. In conclusion, the adoption of eco-briquette technology demonstrates a promising path toward sustainable energy generation and supports broader circular economy objectives.